Patient‐centred care is a way of doing things: How healthcare employees conceptualize patient‐centred care - Fix, Gemmae M.; VanDeusen Lukas, Carol; Bolton, Rendelle E.; Hill, Jennifer N.; Mueller, Nora; LaVela, Sherri L.; Bokhour, Barbara G. (Health expectations : an international journal of public participation in health care and health policy, 2018)
Background Patient‐centred care is now ubiquitous in health services research, and healthcare systems are moving ahead with patient‐centred care implementation. Yet, little is known about how healthcare employees, charged with implementing patient‐centred care, conceptualize what they are implementing. Objective To examine how hospital employees conceptualize patient‐centred care. Research Design We conducted qualitative interviews about patient‐centred care during site four visits, from January to April 2013. Subjects We interviewed 107 employees, including leadership, middle managers, front line providers and staff at four US Veteran Health Administration (VHA) medical centres leading VHA's patient‐centred care transformation. Measures Data were analysed using grounded thematic analysis. Findings were then mapped to established patient‐centred care constructs identified in the literature: taking a biopsychosocial perspective; viewing the patient‐as‐person; sharing power and responsibility; establishing a therapeutic alliance; and viewing the doctor‐as‐person. Results We identified three distinct conceptualizations: (i) those that were well aligned with established patient‐centred care constructs surrounding the clinical encounter; (ii) others that extended conceptualizations of patient‐centred care into the organizational culture, encompassing the entire patient‐experience; and (iii) still others that were poorly aligned with patient‐centred care constructs, reflecting more traditional patient care practices. Conclusions Patient‐centred care ideals have permeated into healthcare systems. Additionally, patient‐centred care has been expanded to encompass a cultural shift in care delivery, beginning with patients' experiences entering a facility. However, some healthcare employees, namely leadership, see patient‐centred care so broadly, it encompasses on‐going hospital initiatives, while others consider patient‐centred care as inherent to specific positions. These latter conceptualizations risk undermining patient‐centred care implementation by limiting transformational initiatives to specific providers or simply repackaging existing programmes.